Organocatalytic, Diastereo- and Enantioselective Synthesis of Nonsymmetric cis-Stilbene Diamines: A Platform for the Preparation of Single-Enantiomer cis-Imidazolines for Protein–Protein Inhibition - Vara, Brandon A. (American Chemical Society, 2014)
[Image: see text] The finding by scientists at Hoffmann-La Roche that cis-imidazolines could disrupt the protein–protein interaction between p53 and MDM2, thereby inducing apoptosis in cancer cells, raised considerable interest in this scaffold over the past decade. Initial routes to these small molecules (i.e., Nutlin-3) provided only the racemic form, with enantiomers being enriched by chromatographic separation using high-pressure liquid chromatography (HPLC) and a chiral stationary phase. Reported here is the first application of an enantioselective aza-Henry approach to nonsymmetric cis-stilbene diamines and cis-imidazolines. Two novel mono(amidine) organocatalysts (MAM) were discovered to provide high levels of enantioselection (>95% ee) across a broad range of substrate combinations. Furthermore, the versatility of the aza-Henry strategy for preparing nonsymmetric cis-imidazolines is illustrated by a comparison of the roles of aryl nitromethane and aryl aldimine in the key step, which revealed unique substrate electronic effects providing direction for aza-Henry substrate–catalyst matching. This method was used to prepare highly substituted cis-4,5-diaryl imidazolines that project unique aromatic rings, and these were evaluated for MDM2-p53 inhibition in a fluorescence polarization assay. The diversification of access to cis-stilbene diamine-derived imidazolines provided by this platform should streamline their further development as chemical tools for disrupting protein–protein interactions.